Spiritual Resilience Through Religious Coping in Overcoming Disruption Value Due to Pandemic Covid-19 at The Jami' Al-Falah Mosque Yogyakarta - Sari, Ramadhanita Mustika; Reza, Iredho Fani (Proceedings of Annual Conference on Community Engagement, 2022)
Issue disruption value due to the pandemic is an interesting thing to study. Because many members of the ta'lim council had to deactivate their routine activities during the Covid 19 pandemic. For two years many Muslim communities felt the value disruption, which affected their religious dimension. The purpose of this service is to realize spiritual resilience in people who experience disruption of religious values. The approach used is religious coping. The religious coping approach (Pargament, 2003) consists of:1) Finding meaning; 2) Self control; 3) Convenienceand closeness to God; 4) Establish relationships with other people and closeness to God; 5) Creating change in life. Researchers try to apply a religious coping approach through participatory action research (PAR) by realizing resilience in Majlis Ta'lim members as a way to overcome disruption values due to the covid-19 pandemic. The conclusion of the results of community service describesthe strategy used in realizing spiritual resilience through religious coping, namely by holding activities at jama’ah Masjid Jami’ Al-Falah Yogyakarta which is divided into five stages: first, the efforts jama’ah Masjid Jami’ Al-Falah Yogyakarta to find meaning. Second, they have self-control. Third, comfort and closeness to God. Fourth, establish relationships with other people and closeness with God. Fifth, there is a change in their life. Of the five stages, an evaluation was then carried out on the results of religious copying and its implementation in overcoming the disruption of religious values in jama’ah Masjid Jami’ Al-Falah Yogyakarta.